Analysis of Vegetation and Structure of Mangrove Community in Ranga-Ranga Village, Banggai Regency, Indonesia - Moh. Fahri Haruna; Abd. Muin Kenta; Riska Masiri; Ibram Ibram; Yuliati R. Ladiku; Nurul Sakinah M. Asiama (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The observed mangrove ecosystem is located in a pond area on the coast of Ranga-ranga Village, Banggai Regency. Therefore, this study aims to provide information on the status of the mangrove ecosystem, including the Important Value Index (INP), Density, Diversity Index, Uniformity, and Dominance. We employed two line transect method measuring 150 meters, plotted 20x20 m, 10x10 m, and 5x5 m, and collected data on environmental factors. The study results show that the mangroves species found are Rhizophora apiculata, R. mucronata, Bruguiera gymnorrhiza, B. sexangula, and Xylocarpus granatum. The highest tree-level INP values are R. apiculata (130,90 %), B. gymnorrhiza (80,24 %), R. mucronata (61,16 %) (80,24 %), Rhizophora mucronata (61,16 %), Bruguiera sexangula (14,39 %), and Xylocarpus granatum (13,31%). At the sapling level, the highest INP values are B. gymnorrhiza (164.75%), R. apiculata (84.75%), R. mucronata (34.89%), and Xylocarpus granatum (15.61%). At the seedling level, the highest INP values are Br. gymnorrhiza (126.06%), R.apiculata (54.52%), and R. mucronata (19.41%). The tree-level community structure has a medium category diversity index, medium category uniformity, and low category dominance. The diversity index is medium at the sapling level, with high category uniformity and low category dominance. At the mangrove seedling level, the diversity index is low category, medium category uniformity, and medium category dominance. The mangrove in research area is in good condition, with dominant species R. apiculata and B. gymnorrhiza. The local government can consider the condition of the mangrove ecosystem in Ranga-ranga Village, Banggai Regency, for adaptive and sustainable management of mangrove areas